The neutrophil-to-lymphocyte ratio and lactate dehydrogenase combined in predicting liver metastasis and prognosis of colorectal cancer - Chen, Qin; Li, Guo-lin; Zhu, Hong-quan; Yu, Jian-Dong; Chen, Zhi-Ping; Wu, Jia-Yan; Lin, Ze-Yu; Wan, Yun-Le (Frontiers in Medicine, 2023)
Background: The neutrophil-to-lymphocyte ratio (NLR) and lactate dehydrogenase (LDH) level are inflammatory markers related to tumour growth and metabolism. This study investigated the value of preoperative NLR, LDH and the combination of NLR and LDH（NLR-LDH） for predicting liver metastasis (CRLM) and tumour prognosis in the early stages of colorectal cancer (CRC). Material and Methods: Three hundred patients undergoing CRC resection were included. Logistic regression analysis was used to estimate the correlation between CRLM time and inflammatory markers, and Kaplan-Meier survival and Cox regression analyses were used to estimate overall survival (OS). Forest plots were prepared based on the multivariate Cox analysis model and evaluated by receiver operating characteristic (ROC) curve analysis. Results: The NLR cut-off value was 2.071according to the ROC curve. The multivariate analysis showed that the elevated LDH level and a high NLR-LDH score were independent predictors of simultaneous CRLM and OS (P<0.05). The combination of a high NLR and elevated LDH and NLR-LDH levels suggested a poor prognosis and a significantly shorter median survival time than a low NLR and low levels of LDH and NLR-LDH. The ROC curve analysis results illustrated that the predictive value of the NLR-LDH score for simultaneous CRLM (area under the curve (AUC)=0.623, P<0.001) and OS (AUC=0.614, P=0.001) was superior to that of the NLR or LDH score used alone. Conclusions: LDH and NLR-LDH are reliable, easy-to-use, independent biomarkers for predicting CRLM and OS in CRC patients. The NLR is an important monitoring index for CRLM. Preoperative NLR, LDH and NLR-LDH may help to guide the use of therapeutic strategies and cancer surveillance.